Integrating immersive media, language learning applications, and interactive activities to enhance English listening and speaking skills: Narrative literature review - Farid Munfaati; Prima Purbasari; Dian Arsitades Wiranegara (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The use of technology-integrated and immersive pedagogies can enhance English listening and speaking skills, and it aids regular classes aiming to improve learner proficiency. Teachers can observe learners' progress, such as reduced anxiety, increased confidence, and better comprehension, once both parties engage with digital tools like podcasts, language learning applications, and online exchange platforms. Aiming to identify effective strategies that address common learner challenges, this study employed a narrative literature review of 45 peer-reviewed articles (2015–2025) selected from Google Scholar and Scopus. Unlike previous reviews that examined listening and speaking separately or focused on a single tool, this study synthesized evidence across three integrated strands: immersive media, language learning applications, and structured interactive activities. The results indicated that these approaches consistently fostered learner engagement and perceived competence, aligning with Krashen's Input Hypothesis and the Affective Filter Hypothesis. As a result, the integration of technology and immersive strategies should not burden teachers or students, as long as the learning process remains efficient. This study advanced existing literature by contributing a conceptual framework (Input, Practice, Interaction, Feedback, and Reflection). At the end of the learning process, students can become lifelong learners despite any conditions they experienced.